Design and Development of Mobile Advertising as A Measure of Advertising and Education Promotion Using Location-Based Service - Mahmud Idris; Tanto (Politeknik Negeri Madiun, 2021)
The use of information technology in business is an important thing to implement in order for businesses to gain competitive advantage. In order to provide superior value to customers or potential customers, companies can implement mobile advertising. Mobile advertising is an advertising service on smartphones and mobile devices that can access content in various forms, from simple text messages to interactive content. This study aims to design a Location-Based Service (LBS) based mobile advertising for advertising and promotion. The method in this study uses the waterfall method with the programming language in this system using Java. This application system runs on the Android operating system. The database used is MySQL. This system can be operated on the Android system to be used for promotion.